A Solid‐Phase Assisted Flow Approach to In Situ Wittig‐Type Olefination Coupling. Issue 29 (4th August 2021) - Tadros, Joseph; Dankers, Christian; Aldrich‐Wright, Janice R.; Polyzos, Anastasios; Gordon, Christopher P.
Abstract: Described herein is the development of a continuous flow, solid‐phase triphenylphosphine (PS‐PPh3 ) assisted protocol to facilitate the in situ coupling of reciprocal pairs of halogen and carbonyl functionalised molecular pairs by a Wittig olefination within 15 mins. The protocol entails injecting a single solution (1 : 1 CHCl3  : EtOH) containing the halogenated and carbonyl‐based substrates into a continuously flowing stream of CHCl3  : EtOH (1 : 1), passed through a fixed bed of K2 CO3 and PS‐PPh3. With advancement to the previous PS‐PPh3 coupling procedures, the method employs a traditional polystyrene‐based immobilisation matrix, the substrate scope of the protocol extended to substituted ketones, secondary alkyl chlorides, and an unprotected maleimide scaffold. Abstract : The development and subsequent application of an in   situ and solid‐phase triphenylphosphine (PS‐PPh3 ) assisted continuous flow protocol to facilitate the coupling of reciprocal primary and secondary halides with aldehyde and ketone‐based substrates is described.